The importance of agricultural training in Hungary (Training and Practice : Journal of Educational Sciences, 2018)
In Hungary – regarding its natural circumstances – all the conditions are given for the operation of the agricultural sectors. Nevertheless, it should be stressed that the agricultural working processes mean particular working conditions. Beyond the specialization of the agricultural sector, it is essential to face the technological and technical development which happened in the last decade, the difficulties of employment, the lack of experts in many cases and the change in the social and economic norms and requirements. During my research it was a starting point to show the number and proportion of workers in the agricultural sector as well as the significant problem concerning this sector, which is the lack of young manpower. The study highlights the fact that unfortunately the qualification of the agricultural workers is quite often unsuitable. In many cases they fulfill their everyday tasks on the basis of practical experience. Emphasizing the importance of the agricultural training the research tries to point out the need for the development and considerable changes in professional training of teachers and subjects so that Hungary could hold a leading position in the world’s food production also in the future.